Cadaveric Temporal Bone Dissection: Is It Obsolete Today? - Naik, Sulabha M.; Naik, Mahendra S.; Bains, Nainjot Kaur (International Archives of Otorhinolaryngology, 2014)
Introduction Traditionally, surgical training in otology, is imparted by dissecting harvested human cadaveric temporal bones. However, maintenance of a cadaveric temporal bone laboratory is expensive and carries risk of exposure to infection. In recent times, other modalities of training are gaining ground and are likely to eventually replace cadaveric temporal bone dissection altogether.Objectives Other alternative methods of training are emerging. New technology like simulation and virtual reality as high-fidelity, safer alternatives, are making rapid strides as teaching tools. Other options are the use of animal temporal bones as teaching tools. The advantages of these are compared.Data Synthesis None of these modalities can replicate the innumerable anatomical variations which are a characteristic feature of the human temporal bone. A novice surgeon not only needs exposure to surgical anatomy and it's variations but also needs to develop hand-eye coordination skills to gain expertise.Conclusion Deliberate practice on human cadaveric temporal bones only, will confer both mastery in anatomy and surgical technique. The human cadaveric temporal bone is ideal simulator for training in otology.
Keywords: cadaver; temporal bone; dissection; simulation